2020
DOI: 10.1097/fjc.0000000000000883
|View full text |Cite
|
Sign up to set email alerts
|

Late Sodium Current in Atrial Cardiomyocytes Contributes to the Induced and Spontaneous Atrial Fibrillation in Rabbit Hearts

Abstract: Increased late sodium current (INa) induces long QT syndrome 3 with increased risk of atrial fibrillation (AF). The role of atrial late INa in the induction of AF and in the treatment of AF was determined in this study. AF parameters were measured in isolated rabbit hearts exposed to late INa enhancer and inhibitors. Late INa from isolated atrial and ventricular myocytes were measured using whole-cell patch-clamp techniques. We found that induced-AF by programmed S1S2 stimulation and spontaneous episodes of AF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Recently, the critical role of atrial energy metabolism remodeling in the occurrence of AF has received attention gradually. The establishment of AF rabbit models here is consistent with the experimental object selected by Chu et al [ 18 ], suggesting the feasibility of taking New Zealand white rabbits as the experimental object. lncRNA sequencing based on nano sensor technology is performed by taking the right atrial muscle tissue of AF/control rabbit model.…”
Section: Discussionsupporting
confidence: 87%
“…Recently, the critical role of atrial energy metabolism remodeling in the occurrence of AF has received attention gradually. The establishment of AF rabbit models here is consistent with the experimental object selected by Chu et al [ 18 ], suggesting the feasibility of taking New Zealand white rabbits as the experimental object. lncRNA sequencing based on nano sensor technology is performed by taking the right atrial muscle tissue of AF/control rabbit model.…”
Section: Discussionsupporting
confidence: 87%
“…In an experimental model of atrial fibrillation induced by ATX-II, a toxin able to enhance I Nalate , it was found that atrial fibrillation was induced by programmed S1-S2 stimulation, and spontaneous episodes of atrial fibrillation were recorded in left atrial tissue exposed to ATX-II, and it was associated with prolonged AP duration in atrial cells, with ranolazine at 10 μM being able to fully eliminate atrial fibrillation. 32 l Nalate is an arrhythmogenic component of the sodium current involved in the genesis of arrhythmias in several animal models of atrial and ventricular heart diseases. 33 In another study, using RA appendages from patients with atrial fibrillation compared with patients with sinus rhythm, it was found that RA cardiomyocytes presented enhanced level of I Nalate .…”
Section: Discussionmentioning
confidence: 99%
“…The resultant sodium influx through late-I Na leads to AP prolongation, and an increase in cytoplasmic sodium concentration [95]. The subsequent sodium/ calcium exchanger (NCX1.1) reverse-mode activity leads to calcium loading within cardiomyocytes [89][90][91][92] resulting in contractile dysfunction, impaired relaxation, activation of pro-hypertrophic gene transcription pathways [96] and ventricular arrhythmias [91,97,98] and AF [99,100] (Fig. 2).…”
Section: Ion Handling In Heart Failure Sudden Cardiac Death and Arrhy...mentioning
confidence: 99%